노인의 건강상태, 건강행위, 사회관계가 건강 관련 삶의 질에 미치는 영향: 가구유형별 분석 - 김영범(Kim Young Bum); 이승희(Lee Seung-hee) (지역사회간호학회지, 2018)
Purpose: The purpose of this study is to identify the effects of the elderly's health statuses, health behavior, and social relations on their health-related quality of life (HRQoL) according to their family types. Methods: The subjects of this study were 1000 elderly persons (298 living alone, 420 living with their spouses, and 282 living with their family)living in C city in Gangwon Province. Data were collected through structured questionnaires from July 20 to September 30, 2015. The SPSS/WIN program was used for data analysis. Results: The HRQoL of the elderly living alone was much lower than the other groups. The most influential factors on the HRQoL include self-rated health and depressive symptoms in all three groups. Social activities and skipping meals were associated with the HRQoL of the elderly living alone and living with their spouses, while marital status, number of chronic disease, and instrumental activities of daily living were associated with the HRQoL of the elderly living with their family. Conclusion: Nurses should take into account family types when designing interventions for improving the HRQoL of the elderly.